Prudent use and antimicrobial prescription practices in Ethiopian veterinary clinics located in different agroecological areas - Takele Beyene Tufa; Kebede Amenu; Nardos Fasil; Fikru Regassa; Tariku J. Beyene; Crawford W. Revie; Henk Hogeveen; J. A. Stegeman (BMC Veterinary Research)
Abstract Background Understanding antimicrobial prescribing (AMP) practices and their prudent use in livestock can support the implementation of stewardship programs in veterinary medicine. Empiric therapy using antimicrobials is widely practiced in resource-poor settings, including Ethiopia. This could significantly contribute to the global burden of antimicrobial resistance (AMR) and the potential accumulation of residues in food. This study assessed AMP practices in Ethiopian veterinary clinics located in different agroecological zones (AEZs) as well as adherence to antimicrobial stewardship principles (ASPs). Methods Data were collected from case book records from four district veterinary clinics located in different AEZs in Ethiopia from 2015 to 2019. To identify factors associated with non-prudent AMP practices (i.e., the use of antimicrobials without therapeutic effects or benefits to the animal), data from registered clinical veterinary cases were selected using a systematic random sampling method. This led to the inclusion of approximately one-third of all records, including animal characteristics, disease symptoms and diagnosis, and details about the prescribed drugs. Descriptive statistics were used to report the proportions of drugs prescribed and adherence to the ASPs. The Chi-square test was used to establish an association between the drugs prescribed and the disease diagnoses and the districts. The factors associated with cases receiving antimicrobials and non-prudent AMP practices were also assessed using a multivariable logistic regression analysis. Results In total, 12,438 clinical case records were considered. Approximately 97% of these cases received treatment without laboratory confirmation, and 15,243 drugs were prescribed. Among these prescriptions, 75% were for antimicrobials, with oxytetracycline (29%) and a combined formulation of penicillin-dihydrostreptomycin (19%) being the most often prescribed drugs. Overall, 19% of the cases were treated non-prudently with antimicrobials, with high incidences at Holeta (32%) and Sekoru (19%) (p < 0.001). Most cases, including viruses and other non-pathogens (100%), toxicants (97%), unknown causes (94%), fungi (70%), nutritional (64%), risk of bacterial infection (42%), and endo-ectoparasites (24%), were treated non-prudently. Cases receiving antimicrobials and non-prudent AMP were associated with Holeta and Sekoru study clinics, major clinical signs of bloat and loss of body condition, and illness due to viral infections (p < 0.05). Conversely, species of animals and cases diagnosed with multiple etiologic agents and respiratory diseases were negatively associated with prudent AMP practices (p < 0.05). Conclusions Much of the prescription practice observed in this study did not adhere to the ASPs; there were significant discrepancies between the prescribed drugs and disease diagnoses. Prescribing antimicrobials for unrelated diagnoses may contribute to an increase in AMR. The study thus underlines the need for mechanisms to improve accurate disease diagnosis and prescriber adherence to prudent AMP in countries with limited resources.